2020
DOI: 10.2147/cmar.s273072
|View full text |Cite
|
Sign up to set email alerts
|

<p>Oncolytic Vaccinia Virus-Mediated Antitumor Effect and Cell Proliferation Were Promoted in PTC by Regulating circRNA_103598/miR-23a-3p/IL-6 Axis</p>

Abstract: Background: Papillary thyroid carcinoma (PTC) is the most common type of thyroid malignancy, and cases have been rising steadily worldwide in the past few decades. Despite great progress having been made in surgery and chemotherapy for PTC, the survival rate of PTC patients has not increased significantly. Therefore, there is an urgent need to explore novel treatment strategies. Materials and Methods: The levels of circRNA_103598, miR-23a-3p and IL-6 mRNA in PTC tissues and cells were examined by qRT-PCR assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Similarly, circEIF6 knockdown effectively reduced tumor weight in the nude mice treating with cisplatin, while circEIF6 knockdown alone had no effect on tumor weight ( Liu et al, 2018 ). Moreover, Zhang S. et al (2020) revealed that circRNA_103598 increased as a regulator increasing the expression of IL-6 via sponging miR-23a-3p in PTC, with promoted cell proliferation and the enhanced oncolytic vaccinia virus (OVV)-mediated antitumor effect by strengthening the viral replication.…”
Section: Roles and Significance Of Circrnas In Tcmentioning
confidence: 99%
“…Similarly, circEIF6 knockdown effectively reduced tumor weight in the nude mice treating with cisplatin, while circEIF6 knockdown alone had no effect on tumor weight ( Liu et al, 2018 ). Moreover, Zhang S. et al (2020) revealed that circRNA_103598 increased as a regulator increasing the expression of IL-6 via sponging miR-23a-3p in PTC, with promoted cell proliferation and the enhanced oncolytic vaccinia virus (OVV)-mediated antitumor effect by strengthening the viral replication.…”
Section: Roles and Significance Of Circrnas In Tcmentioning
confidence: 99%
“…As the results, the new focus is on targeting the immune response, rather than the tumor itself [12]. A series of studies have shown that vaccinia virus can not only directly lyse tumor cells [13,14], but also initiate the anti-tumor immune responses [15][16][17]. On the other hand, several studies indicated that C-type lectin could enhance the immune response [18,19].…”
Section: Introductionmentioning
confidence: 99%